Two-dimensional Fast Surface Imaging Using a Handheld Optical Device: In Vitro and In Vivo Fluorescence Studies - Erickson, Sarah J (Neoplasia Press Inc., 2010)
Near-infrared (NIR) optical imaging is a noninvasive and nonionizing modality that is emerging as a diagnostic tool for breast cancer. The handheld optical devices developed to date using the NIR technology are predominantly developed for spectroscopic applications. A novel handheld probe-based optical imaging device has been recently developed toward area imaging and tomography applications. The three-dimensional (3D) tomographic imaging capabilities of the device have been demonstrated from previous fluorescence studies on tissue phantoms. In the current work, fluorescence imaging studies are performed on tissue phantoms, in vitro, and in vivo tissue models to demonstrate the fast two-dimensional (2D) surface imaging capabilities of this flexible handheld-based optical imaging device, toward clinical breast imaging studies. Preliminary experiments were performed using target(s) of varying volume (0.23 and 0.45 cm(3)) and depth (1–2 cm), using indocyanine green as the fluorescence contrast agent in liquid phantom, in vitro, and in vivo tissue models. The feasibility of fast 2D surface imaging (∼5 seconds) over large surface areas of 36 cm(2) was demonstrated from various tissue models. The surface images could differentiate the target(s) from the background, allowing a rough estimate of the target's location before extensive 3D tomographic analysis (future studies).